Contouring and augmentation of the temple using stromal vascular fraction gel grafting - Zhang, Yuchen; Zou, Jialiang; Yuan, Yi; Gao, Jianhua; Chen, Xihang (Frontiers in Surgery, 2022)
Background: Hollowing temples are common in aging Asians. Stromal vascular fraction (SVF) gel is a novel, mechanically processed adipose-derived product containing condensed adipose-derived stem cells and native extracellular matrix, allowing improved fat grafting. The present study evaluated the effectiveness of SVF-gel treatment on temple hollowing. Methods: This prospective, single-center study included an SVF-gel grafting group (n = 34) and a Coleman’s fat grafting group (n = 29). Temple contour was assessed using preoperative and postoperative photographs. Temple augmentation was quantified using three-dimensional (3D) technology and an MVS-600 3D scanner system. Patient satisfaction was assessed postoperatively. Results: At 12 months follow-up, the minimal forehead width/forehead width ratio and the width of the temporal peak were increased in both groups (p < 0.05).; and the retention rate (41.2% ± 8.4%) of the SVF-gel group was significantly higher than that of Coleman’s fat group (32.6% ± 8.8%; p < 0.05). Moreover, patients in the SVF-gel group reported higher satisfaction scores than those in Coleman’s fat group. Conclusions: SVF-gel is effective for temple contouring and augmentation., with increased efficacy compared with Coleman’s fat.